Exploring Dendroflora Diversity and Ecology in an Urban Arboretum from Western Romania: The Role of Plant Life-Form and Plant Family in Urban Woody Phytocoenosis - Madalina Iordache; Laurentiu Zamfir; Alexandra Becherescu; Ana Codruţa Chiş (Plants)
The dendroflora of an urban arboretum (The Botanic Park of Timișoara, Romania), consisting of 193 species, was ecologically characterized as bioforms, phytogeographical elements, and preferences for moisture, temperature, and soil pH. The aim of the research was to determine whether the native ecological requirements of the woody species, along with certain biological and evolutionary traits of them, such as plant life-form and plant family, could serve as tools for explaining and understanding the strategies employed by the urban woody phytocoenoses to acclimate and adapt to an established environment, such as an urban arboretum. The inventoried species are grouped in 111 genera and 45 families. The native and non-native dendroflora share 16 common families. The most representative family both in the native and non-native dendroflora is Rosaceae. The monotypic families are largely present (22.22% in the native dendroflora, and 42.22% in the non-native dendroflora). The plant life-form spectrum is dominated by megaphanerophytes (49%), followed by mesophanerophytes (41%). The chorological spectrum of the native species comprises 16 chorological types and is dominated by Eurasians (32%) and Europeans (30%). The species characteristics of the Pontic-Carpathian space, to which Romania belongs, are rare in the analyzed urban botanical park (4%). The mesophyte, mesothermal and slightly acido-neutrophilous species dominate both the native and non-native dendroflora. In the acclimation process of the non-native dendroflora, 37% of species exceeded their native requirements for moisture, 41% for temperature, and 50% for soil pH. The species requirements for temperature are associated to those for moisture and soil pH. The results show the potential of the analysed woody species to exceed their native requirements within the acclimation and adaption process, and in this process, for the studied temperate site, the plant life-form is important, and also the plant family. The species of the analyzed urban arboretum, both native and non-native, are taxonomically and biogeographically diverse, with specific habitat requirements, suggesting their great ability in acclimating, adapting and resisting.